Analisa Penataan Ruang Pada Pasar Raya I Salatiga - Masayu, Murista Mutiara; Rukayah , R. Siti (Department of Architecture, Faculty of Science and Technology, Alauddin State Islamic University, 2025)
A traditional market is a place where traders and buyers gather, characterized by direct transactions between them. Traditional markets typically consist of stalls or outlets, los (permanent or semi-permanent trading spaces), and open areas. One city that still heavily relies on markets for its economy is Salatiga. Pasar Raya I Salatiga is one of the largest markets in the city, comprising 69 shop houses, 240 stalls, and 2,150 los. However, the number of these facilities is not proportional to the number of traders currently operating there. One contributing factor is the suboptimal utilization of planned spaces. Initial observations at Pasar Raya I Salatiga reveal the presence of underutilized areas (commonly referred to as